2017
DOI: 10.1017/s0030605317000333
|View full text |Cite
|
Sign up to set email alerts
|

Bushmeat consumption and environmental awareness in rural households: a case study around Taï National Park, Côte d'Ivoire

Abstract: Consumption of bushmeat, a staple food of people living in the vicinity of protected areas, is a challenge for the conservation of wildlife. The underlying factors driving this consumption are, however, relatively understudied, particularly among rural households, and improved understanding would facilitate the development of conservation strategies. We therefore aimed to identify the factors that influence bushmeat consumption in rural households to the west of Taï National Park, in Côte d'Ivoire. We carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 32 publications
3
27
0
2
Order By: Relevance
“…Our findings also indicate that if patrolling effort is not high enough, wildlife populations will continue to decrease in the face of increasing human pressures. However, we also believe that other factors, such as changing people's behaviour through awareness raising, are also important to consider for wildlife protection (Kouassi et al, 2017). We have used a novel approach, collecting data on wildlife and illegal activity independently of patrolling data; however, the measure we used to estimate patrolling effort is coarse and does not take into account the precise location of patrols.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also indicate that if patrolling effort is not high enough, wildlife populations will continue to decrease in the face of increasing human pressures. However, we also believe that other factors, such as changing people's behaviour through awareness raising, are also important to consider for wildlife protection (Kouassi et al, 2017). We have used a novel approach, collecting data on wildlife and illegal activity independently of patrolling data; however, the measure we used to estimate patrolling effort is coarse and does not take into account the precise location of patrols.…”
Section: Discussionmentioning
confidence: 99%
“…Since we found high consistencies and no evidence of intentional underreporting of species with higher protection status (e.g. 7.3% vs. 7%, Kouassi et al., 2017 utilization of primates), we assume that our dataset accurately reflects reality (Appendix 1.2, Table A1.2) and is suitable to answer our research questions. See also Bachmann et al.…”
Section: Methodsmentioning
confidence: 96%
“…Lastly, the amount of meat required to fulfil household protein and micronutrient requirements can increase reliance on bushmeat and affect selectivity (Friant et al., 2020). We therefore included the number of dependent children per household, as the pressure to provide nourishment or money may be higher for households with more mouths to feed (Bachmann et al., 2019; Kouassi et al., 2017; Overview see Table 2, summary statistic Appendix Tables A.1.4–A.1.6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important conservation intervention includes awareness raising activities, especially because in certain areas medicinal or magical properties are assigned to chimpanzee parts and chimpanzee bone powder (Hanson-Alp et al, 2003). There are studies that have shown a positive effect of such interventions on bushmeat consumption, for example in the context of repeated multimedia campaigns (Kouassi et al, 2017) and Ebola information campaigns (Ordaz-Németh et al, 2017). However, hunting chimpanzees is also strongly driven by a demand for chimpanzee parts and live animals from urban areas and even international markets (Kuehl et al, 2009;Greengrass, 2016;Strindberg et al, 2018).…”
Section: Threat Reduction Through Behavioral Changementioning
confidence: 99%